CULTIVATION OF WINTER WHEAT IN THE CONDITIONS OF NEWLY MAINTAINED DESERT ZONE SOILS BASED ON ECONOMICAL IRRIGATION TECHNOLOGY - А. K. Juraev; O. M. Yusupova (Bright Mind Publishing, 2025)
This article presents the results of using a highly swelling hydrogel polymer compound, synthesized from local raw materials, as a water-saving irrigation technology. The study focused on the cultivation of the winter wheat variety “Starshina” under different standards in the gray-brown, light sand, non-saline soils of the newly developed desert zone in the Bukhara region. The research also explored the impact of seasonal irrigation standards on winter wheat.
Keywords: Winter wheat, hydrogel, polymer, compound, irrigation, grain, water saver.